Penegakan Hukum terhadap Pelanggaran Izin Reklame di Kota Makassar (Studi Kasus di Kota Makassar) - Indrahayu M Umar Gazali; Maemanah (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to find out how law enforcement is against violations of advertising permits in Makassar City and to find out what factors influence the effectiveness of law enforcement against violations of advertising permits in Makassar City. the type of research used in this study is empirical research because in this study the data was obtained directly from the field and combined with laws and regulations. Primary data in the form of data obtained from interviews with research subjects and secondary data obtained from local regulations. The results of this study indicate that in general law enforcement carried out by the local government related to the implementation of advertising for those who have permits has been running well, but is still lacking, such as the imposition of sanctions for organizers who do not have permits due to the absence of regulations governing the imposition of sanctions for organizers who do not have permits. In addition, in its implementation, several factors become obstacles in increasing the effectiveness of advertising permit enforcement such as legal products, law enforcers, and the community. However, there are also factors that support the increase in the effectiveness of advertising permit enforcement such as supporting facilities and infrastructure provided by the local government to the Arrangement and Control Team. This study recommends the need to hold socialization or education to increase the level of legal awareness embedded in the community, and the government is expected to make new regulations related to the imposition of sanctions for advertising organizers who do not have permits, and the government can also, if necessary, review the types of sanctions given by advertising organizers by providing heavier/firmer sanctions and not being selective.